Exploring quality dimensions from a construction perspective: a literature review - Abubakar, Abdurrahman Salihu; Haron, Nuzul Azam; Alias, Aidi Hizami; Teik Hua, Law (Penerbit UTM Press, 2023)
The quality of products and services is fundamental to organizational performance and reputation. A construction project entails meeting the specification criteria and standards of quality, finishing the task on time, and within the specified budget. Construction projects have different quality dimensions, and each can be measured from a different perspective. An exploratory research approach was used to explore the eight quality dimensions within the construction industry's perspective by exploring the quality issues within the Malaysian construction industry. The findings indicate that a related quality dimension is conformance or the degree to which a product's design and operating characteristics meet established standards. Thus, the study's significant contribution is the exploration of the eight quality dimensions from the construction industry's perspective. Thus, it is essential to ensure that the project meets the users' needs, and the best way to do this is to involve the users in the quality planning process. This will help ensure the project is designed and built to meet their needs and expectations. In conclusion, considering all the quality dimensions when planning and executing a construction project is essential, and by prioritizing these quality dimensions, we can ensure that the buildings are built with quality.